Multicultural Leadership of School Principles in The Digital Age - Sugiarto Sugiarto (STAI Miftahul Ula Nganjuk, 2022)
In Indonesia, with 17,504 islands spread over 34 provinces, 1,340 tribes, 300 tribes, and 742 languages, multicultural communities like this are common and easy to find throughout the country. Multicultural communities can lead to three views as a principal school pandana. The problem that often arises is that there is no guarantee that social conflict can be avoided, even though Indonesians live harmoniously. The research method is a combined research method, in which quantitative and qualitative research methods are combined into one. The development of information technology in the digital era can be used as a tool in school management. This research was carried out in basic education in the DKI Jakarta province from January 2022 to June 2022. The results were obtaining information on needs and an overview of school principals' multicultural personalities and leadership. Suggestions on the dimensions of multicultural personality, which are still low, can be made to improve it, considering that the multicultural personality possessed by the principal can improve his ability to implement multicultural education in the school he leads. The implication is that the principal will have various information related to multiculturalism.